2004
DOI: 10.1021/jf040181e
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Trichothecene Production, Genetic Variability, and Virulence to Wheat of Fusarium graminearum from Smallholder Farms in Nepal

Abstract: Fusarium graminearum causes wheat head blight and contaminates grain with the trichothecenes 4-deoxynivalenol and nivalenol. Sequence analysis of trichothecene genes indicates that nivalenol production is the ancestral trait; however, deoxynivalenol producers occur worldwide and predominate in North and South America and in Europe. Analysis of a large field population (>500 strains) from Nepal identified three groups that were both genetically distinct and polymorphic for trichothecene production: SCAR1 compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 34 publications
(75 reference statements)
1
18
0
Order By: Relevance
“…1). The physical locations of TRI5, TRI15, and the SCAR marker were consistent with the previous linkage analyses (1,11,19). The structural genes MGV1, PHO, RED, and TRI101 also were located in expected positions on the physical map.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…1). The physical locations of TRI5, TRI15, and the SCAR marker were consistent with the previous linkage analyses (1,11,19). The structural genes MGV1, PHO, RED, and TRI101 also were located in expected positions on the physical map.…”
Section: Discussionsupporting
confidence: 88%
“…These genetic conclusions were confirmed by Lee et al (25), who showed that TRI13 determines which toxin type is produced and that this locus is located in the trichothecene cluster near TRI5. Alexander et al (1) used the map to locate Tri15 on LG 2, and Desjardins et al (11) used the map to locate a diagnostic SCAR marker locus on LG 5. The genetic map also was used to map loci for pathogenicity and aggressiveness of G. zeae toward wheat (8).…”
mentioning
confidence: 99%
“…In particular the relative frequency of DON and NIV is of concern because recent reports suggest that strains of ND 4618 13 IIN ND ND ND ND ND ND 4624 14 IIS ND ND ND ND ND ND 4625 14 IIS ND ND ND ND ND ND 4627 14 IIS ND ND ND ND ND ND 4628 14 IIS ND ND ND ND ND ND 4631 9 IIS ND ND ND ND ND ND 4633 9 IIS ND ND ND ND ND ND 4605 7 IV ND ND ND ND ND ND the F. graminearum complex that produce NIV may be more aggressive towards corn but less aggressive to wheat than DON producing strains. These results indicate that there may be important consequences for the fitness and aggressiveness of FHB pathogens of different chemotype on particular hosts (3,7,11). Further studies will be necessary in order to characterize the genetic diversity, chemotype and virulence of F. graminearum populations from Argentina, a country where this species is widespread and wheat is cultivated under different agro-meteorological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In planta, trichothecenes are known to act by blocking the synthesis of proteins and favor pathogen colonization in host tissue (Desjardins et al, 1993;Desjardins et al, 1996). Moreover, DON is recognized as a virulence factor during pathogenesis, with more symptoms being associated with higher DON production, whereas NIV in wheat is produced in smaller quantities than DON (Desjardins et al, 2004).…”
Section: Central-spikelet Inoculation Assaymentioning
confidence: 99%